2012
DOI: 10.1111/j.1439-037x.2012.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Maize Hybrid Variability for Transpiration Decrease with Progressive Soil Drying

Abstract: Drought is ubiquitous in rainfed cropping systems and often limits maize yields. The sensitivity of transpiration response early in progressive soil drying is a trait with potential to improve crop drought resistance. Simulation studies demonstrated that increased sensitivity to drying soil leading to restricted transpiration rates results in conservation of soil water during vegetative stages for possible use during grain filling. In contrast to other crops, there have been no studies characterizing genotypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…Br.) genotypes, that the threshold ranged from 0.30 to 0.47, and Gholipoor et al (2012b) found, in a comparison of 36 maize ( Zea mays L.) hybrids, a threshold range of 0.33 to 0.60. Those genotypes with a high threshold seemingly have the capacity to conserve soil water during soil‐drying events early in the growing season so that soil water remains during grain filling to allow sustained growth and expression of the stay‐green phenotype.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Br.) genotypes, that the threshold ranged from 0.30 to 0.47, and Gholipoor et al (2012b) found, in a comparison of 36 maize ( Zea mays L.) hybrids, a threshold range of 0.33 to 0.60. Those genotypes with a high threshold seemingly have the capacity to conserve soil water during soil‐drying events early in the growing season so that soil water remains during grain filling to allow sustained growth and expression of the stay‐green phenotype.…”
mentioning
confidence: 85%
“…Similar results were demonstrated in pearl millet, in that a genotype tolerant to drought expressed limited‐transpiration trait at high VPD (>2.0 kPa) (Kholova et al, 2010). Gholipoor et al (2012b) examined the response to increasing VPD of 35 maize hybrids and found 11 expressed the maximum transpiration trait with the breakpoint for the limitation on transpiration occurring at 1.7 to 2.5 kPa.…”
mentioning
confidence: 99%
“…In a study by Gholipoor et al (2013), sap flow measurements proved an accurate indicator of the water flow and transpiration rates relative to abiotic stress parameters (drought and intensity of light) for maize. With increased evapotranspiration requirements (depending on the daily variation in global solar radiation and air temperature), the transpiration rate was higher compared with the rates under water-stressed conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The transpiration of plants decreased during both daily and seasonal periods with decreasing soil water content in relation to the evapotranspiration conditions of the environment. The sensitivity threshold of maize transpiration to the availability of soil moisture may also be influenced by the genotype (Gholipoor et al 2013;Leitner et al 2014). Compared with the soil moisture content at full field capacity, an AWHC decrease of 20% resulted in a statistically significant decrease in the amount of transpired water by maize plants (Wu et al 2011b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation